Emilia Pardo Bazán; Prudencio Canitrot; Biography; Relationships; Disagrees. - Groba Bouza, Fernando; Vázquez Corral, Antón (Madrygal. Revista de Estudios Gallegos, 2016)
This study provides 183 terms related to the Galician equine sector, collected in a field study conducted all over Galicia for a time span of three years. These terms will be compared to two reference works on current Galician lexicography and terminography. In addition, this terminographical and lexicographical study contains data on the geographical distribution of the said terms as well as grammatical categories and their semantic fields. The words that form the cornerstone of this work come with their own definition, where and when they were collected, an example of usage, and an illustration.
Keywords: Terminology; Lexicology; Terminography; Lexicography; Equine Vocabulary.